Trapping of European buprestid beetles in oak forests using visual and olfactory cues. Issue 2 (2nd July 2013) - Domingue, Michael J.; Imrei, Zoltán; Lelito, Jonathan P.; Muskovits, József; Janik, Gergely; Csóka, György; Mastro, Victor C.; Baker, Thomas C.
Abstract Trapping approaches developed for the emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae), were adapted for trapping several European oak buprestid species. These approaches included the use of natural leaf surfaces as well as green and purple plastic in sticky trap designs. Plastic surfaces were incorporated into novel 'branch‐trap' designs that each presented two 5 × 9‐cm2 rectangular surfaces on a cardboard structure wrapped around the leaves of a branch. We used visual adult Agrilus decoys in an attempt to evoke male mating approaches toward the traps. Our first experiment compared the attractiveness of visual characteristics of the surfaces of branch‐traps. The second looked at the effect on trap captures of adding semiochemical lures, including manuka oil, (Z)‐3‐hexen‐1‐ol, and (Z)‐9‐tricosene. In total, 1 962 buprestid specimens including 14 species from the genus Agrilus were caught on 178 traps in a 22‐day time‐span. Overall, the green plastic‐covered branch‐traps significantly out‐performed the other trap designs. We further found that the presence of an EAB visual decoy placed on the trap surface often increased captures on these green traps, but this effect was stronger for certain Agrilus species than for others. The visual decoy was particularly important for the most serious pest detected, Agrilus biguttatus Fabricius, which was captured 13 times on traps with decoys, but only once without a decoy. There were some small but significant effects of odor treatment on the capture of buprestids of two common species, Agrilus angustulus Illiger and Agrilus sulcicollis Lacordaire. There were also 141 Elateridae specimens on these traps, which were not influenced by trap type or decoys. The results suggest that small branch‐traps of this nature can provide a useful new tool for monitoring of buprestids, which have the potential to be further optimized with respect to visual and olfactory cues.